HOW THE UNIVERSITIES CAN AID THE ACCOUNTING PROFESSION. - Belser, F. C. (The Accounting Review, 1927)
Abstract In spite of the multiplication of schools of accountancy during the last twenty-five years, a relatively small percentage of the men who enter the profession have graduated from the recognized schools. This is no doubt due in large part to a lack of cooperation between the school and the profession for a purpose which would be mutually advantageous. Some progress is this respect has been made in the last few years by the establishment of a Bureau of Placements by the American Institute of Accountants, but the conditions of employment laid down there in leave much to be desired, and seem designed rather to give the student control of his position instead of permitting the employer to control the student. To illustrate how important is the correlation of theory with practice, it is only necessary to point out that in any given piece of work it would be practically an endless task to carry out in full every operation and every test which the theory would make possible. An audit carried out along these lines would be prohibitive in cost, and its result would be no more certain.